The Long‐Term Robustness and Stability of Consensus Values as Composition Location Estimators for a Typical Geochemical Test Material in the GeoPT Proficiency Testing Programme. Issue 3 (7th May 2019) - Webb, Peter C.; Potts, Philip J.; Thompson, Michael; Wilson, Stephen A.; Gowing, Charles J. B.
Abstract : Re‐issuing the same test material, its true identity unknown to participants, in two rounds of the Geo PT proficiency testing programme 18 years apart has demonstrated remarkable similarity, and therefore stability, of consensus values independently estimated for over fifty measurands in each round. A comparison of the two data sets, Geo PT 5 (AMH‐1) from 1999 and Geo PT 41 (ORA‐1) from 2017, shows that corresponding consensus values, rigorously derived by current procedures for complete compatibility, are for the most part statistically indistinguishable when account is taken of their associated uncertainties. Inferences that may be drawn from this exceptional agreement include: (a) the consensus estimation procedure was robust and gave consistent results; (b) overall, the balance of the contributed data was unaffected by significant changes in: (i) the populations of laboratories participating, (ii) the proportions of laboratories producing results by different techniques, (iii) the manner in which systems were calibrated, or (iv) the aspirations of laboratories to attain higher quality results over time; and (c) unsurprisingly perhaps, that the test material itself had remained stable and unchanged during that time. Additionally, a statistical comparison of the original values for AMH‐1 with consensus values derived by current procedures demonstrates that they are also effectively indistinguishable. Key Points: Re‐issuing the same test material in two rounds of the Geo PT proficiency testing programme 18 years apart has provided statistically indistinguishable consensus values for over 50 measurands. Equivalent consensus values were observed despite changes in participating laboratories, methods used and advances in analytical methodology. This result demonstrates the outstanding stability of results from the Geo PT proficiency testing scheme.